Expert Consensus on the Diagnosis and Treatment of FGFR Gene-Altered Solid Tumors - Xu, Chunwei; Lian, Bin; Ou, Juanjuan; Wang, Qian; Wang, Wenxian; Wang, Ke; Wang, Dong; Song, Zhengbo; Liu, Aijun; Yu, Jinpu; Zhong, Wenzhao; Wang, Zhijie; Zhang, Yongchang; Liu, Jingjing; Zhang, Shirong; Cai, Xiuyu; Liu, Anwen; Li, Wen; Mao, Lili; Zhan, Ping; Liu, Hongbing; Lv, Tangfeng; Miao, Liyun; Min, Lingfeng; Chen, Yu; Yuan, Jingping; Wang, Feng; Jiang, Zhansheng; Lin, Gen; Huang, Long; Pu, Xingxiang; Lin, Rongbo; Liu, Weifeng; Rao, Chuangzhou; Lv, Dongqing; Yu, Zongyang; Li, Xiaoyan; Tang, Chuanhao; Zhou, Chengzhi; Zhang, Junping; Xue, Junli; Guo, Hui; Chu, Qian; Meng, Rui; Wu, Jingxun; Zhang, Rui; Zhou, Jin; Zhu, Zhengfei; Li, Yongheng; Qiu, Hong; Xia, Fan; Lu, Yuanyuan; Chen, Xiaofeng; Ge, Rui; Dai, Enyong; Han, Yu; Pan, Weiwei; Pang, Fei; Huang, Jintao; Wang, Kai; Wu, Fan; Xu, Bingwei; Wang, Liping; Zhu, Youcai; Lin, Li; Xie, Yanru; Lin, Xinqing; Cai, Jing; Xu, Ling; Li, Jisheng; Jiao, Xiaodong; Li, Kainan; Wei, Jia; Feng, Huijing; Wang, Lin; Du, Yingying; Yao, Wang; Shi, Xuefei; Niu, Xiaomin; Yuan, Dongmei; Yao, Yanwen; Huang, Jianhui; Feng, Yue; Zhang, Yinbin; Sun, Pingli; Wang, Hong; Ye, Mingxiang; Wang, Zhaofeng; Hao, Yue; Wang, Zhen; Wan, Bin; Lv, Donglai; Zhai, Zhanqiang; Yang, Shengjie; Kang, Jing; Zhang, Jiatao; Zhang, Chao; Shi, Lin; Wang, Yina; Li, Bihui; Zhang, Zhang; Li, Zhongwu; Liu, Zhefeng; Yang, Nong; Wu, Lin; Wang, Huijuan; Jin, Gu; Wang, Guansong; Wang, Jiandong; Fang, Meiyu; Fang, Yong; Li, Yuan; Wang, Xiaojia; Chen, Jing; Zhang, Yiping; Zhu, Xixu; Shen, Yi; Ma, Shenglin; Wang, Biyun; Si, Lu; Lu, Yuanzhi; Li, Ziming; Fang, Wenfeng; Song, Yong (Global Medical Genetics, 2024)
The fibroblast growth factor receptor (FGFR) is a crucial receptor tyrosine kinase involved in essential biological processes, including growth, development, and tissue repair. However, FGFR gene mutations, including amplification, fusion, and mutation, can disrupt epigenetics, transcriptional regulation, and tumor microenvironment interactions, leading to cancer development. Targeting these kinase mutations with small molecule drugs or antibodies has shown clinical benefits. For example, erdafitinib is approved for treating locally advanced or metastatic urothelial cancer patients with FGFR2/FGFR3 mutations, and pemigatinib is approved for treating cholangiocarcinoma with FGFR2 fusion/rearrangement. Effective screening of FGFR variant patients is crucial for the clinical application of FGFR inhibitors. Various detection methods, such as polymerase chain reaction, next-generation sequencing, fluorescence in situ hybridization, and immunohistochemistry, are available, and their selection should be based on diagnostic and treatment decision-making needs. Our developed expert consensus aims to standardize the diagnosis and treatment process for FGFR gene mutations and facilitate the practical application of FGFR inhibitors in clinical practice.
Keywords: solid tumors; tyrosine receptor kinase; precision medicine; targeted therapy